Capital structure determinants of Shariah-compliant firms: Malaysian evidence - Sahudin, Zahariah; Wan Mahmood, Wan Mansor; Haron, Razali; Isa, Zaidi (2015)
The objective of this study is to examine the determinants of capital structure of Shariah-compliant firms in Malaysia using the static framework. The study also analysed the impact of sector specific and country specific factor on the corporate financing decisions within the Shariah-compliant firms. The introduction of sector specific factor, Herfindahl-Hirschman Index and country specific factors such as the stock market development level, rates of interest and growth domestic product (GDP) enriches these results. The importance of sector specific and country specific factor were also documented in this study. The impact of those factors on the capital structures appeared to be inconsistent among these Shariah-compliant firms. It is therefore apparent that capital structure decision is not only the consequence of the firm’s own characteristics only, but it is also due to the impact of sector and institutional environment in which the firm operates and these Shariah-compliant firms are no exception.